The Effect of Profitability, Leverage on Firm Value and Corporate Social Responsibility (CSR) as a Moderating Variable - Abdullah Nasih Ulwan; Acep Komara; Krisdiana; Efi Deayu (PT FORMOSA CENDEKIA GLOBAL, 2025)
Firm value is commonly understood as an indicator of a company’s market performance, typically reflected through movements in its share price. This study seeks to examine the influence of profitability and leverage on firm value, while also evaluating the moderating role of Corporate Social Responsibility (CSR). The research focuses on companies within the energy sector—specifically those operating in the mining sub-sector—that were publicly listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. A purposive sampling technique was employed to select nine companies that met the study’s criteria. The research adopts a quantitative approach, with data analysed using EViews 12 through both multiple regression analysis and moderated regression analysis (MRA). The empirical results reveal that Return on Assets (ROA) does not have a statistically significant effect on firm value. Conversely, leverage demonstrates a significant and positive relationship. Additionally, CSR is found not to significantly moderate the relationship between either profitability or leverage and firm value, suggesting a limited moderating effect within the scope of this analysis.